Pengaruh pertumbuhan ekonomi terhadap ketimpangan pendapatan dan kemiskinan (studi provinsi-provinsi di Indonesia) - Istiqamah Istiqamah; Syaparuddin Syaparuddin; Selamet Rahmadi (e-Jurnal Perspektif Ekonomi dan Pembangunan Daerah, 2018)
This study aims to analyze: 1) the effect of economic growth on income inequality of provinces in Indonesia; 2) the effect of economic growth on the poverty of provinces in Indonesia. The data used are secondary data which includes time series data for 2010-2016 and cross section data of 34 provinces in Indonesia. Data were analyzed by panel data regression. The results of the analysis found that increasing economic growth led to increased income inequality and the number of poor people in the provinces in Indonesia.